2009
DOI: 10.3866/pku.whxb20090619
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of TiO<sub>2</sub> Films with Rutile/Anatase Mixed Crystal Structures

Abstract: Agroupofnano鄄TiO 2 filmcatalystswithrutile/anatasemixedcrystalstructureswerepreparedbya magnetronsputteringmethod.Thephotodegradationofphenolwasemployedtoevaluatethephotocatalyticactivities ofthefilmcatalysts.Withlessrutilecontentinthecatalysts,photocatalyticactivitiesimprovedgradually.Filmproperties wereinvestigatedusingX 鄄 raydiffraction(XRD),X 鄄 rayphotoelectronspectroscopy(XPS),surfacephotovoltage spectroscopy(SPS)andatomicforcemicroscopy(AFM).Resultsindicatethatallfilmshavearutile/anatasemixedcrystal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been reported that the photocatalytic activities of TiO2 thin film composed by the mixed phase of rutile and anatase increase with the increasing content of anatase. 27,28 Simultaneously, if the Ar/O2 flow ratios were kept constant, then TiO2 thin film deposited at 2.0 Pa would show that the amounts of the generated acetone and CO2 were the largest. As evident from Fig.6, TiO2 film deposited at 2.0 Pa with the Ar/O2 flow ratio of 1:1 showed the highest photocatalytic activity.…”
Section: Vol28mentioning
confidence: 99%
“…It has been reported that the photocatalytic activities of TiO2 thin film composed by the mixed phase of rutile and anatase increase with the increasing content of anatase. 27,28 Simultaneously, if the Ar/O2 flow ratios were kept constant, then TiO2 thin film deposited at 2.0 Pa would show that the amounts of the generated acetone and CO2 were the largest. As evident from Fig.6, TiO2 film deposited at 2.0 Pa with the Ar/O2 flow ratio of 1:1 showed the highest photocatalytic activity.…”
Section: Vol28mentioning
confidence: 99%